Amorphous/crystalline silicon heterojunction solar cells with black silicon texture. Issue 10 (30th July 2014) - Mews, Mathias; Leendertz, Caspar; Algasinger, Michael; Koynov, Svetoslav; Korte, Lars
<x xml:space="preserve">Abstract</x> Excellent passivation of black silicon surfaces by thin amorphous silicon layers deposited with plasma enhanced chemical vapor deposition is demonstrated. Minority charge carrier lifetimes of 1.3 milliseconds, enabling an implied open‐circuit voltage of 714 mV, were achieved. The influence of amorphous silicon parasitic epitaxial growth and thickness, as well as of the texture depth is investigated. Furthermore, quantum efficiency gains for wavelengths above 600 nm, as compared to random textured solar cells, are demonstrated in 17.2% efficient amorphous–crystalline silicon heterojunction solar cells with black silicon texture. (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)